Empowerment of PKK Mothers on Assisting Pregnant Women in Conducting Antenatal Care Visits - Hariati, Mayang Citra; Yosepha Ginting, Desideria; Arisman, Yessy; Era, Elvi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Antenatal Care (ANC) is a form of service provided by midwives to pregnant women with the aim that every pregnant woman gets integrated, comprehensive, quality services and provides counseling, information and education to mothers during pregnancy. Pregnancy examination in pregnant women is actually preventive and aims to detect early if there are abnormalities or diseases suffered by mothers during pregnancy so that midwives can intervene quickly and appropriately against these diseases and disorders and midwives can make referrals to more complete and adequate health facilities in accordance with the applicable referral system. Pregnancy check-up or antenatal care can also be a means for midwives to carry out health promotion and health education about healthy pregnancy, safe and comfortable childbirth and also how to prepare for parenthood. The standard care for antenatal care consists of weight weighing, blood pressure measurement, fundus uterine height measurement, Fe tablets as much as 90 tablets during pregnancy, tetanus toxoid immunization, haemoglobin (Hb) examination, VDRL examination, breast care, breast gymnastics and breast press massage, maintenance of fitness level or pregnancy exercises, talks, urine protein examination, administration of iodine capsule therapy for goiter endemic, administration of anti-malarial therapy for malaria-endemic areas.